The ways of modern word formative processes as reflection of worldview - Курушина, Марина Анатоліївна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”)
The article examines the main ways of studying word formative processes in line with cognitive linguistic. The author thinks that languages are the different ones not only as tools for constructing the speech, but also as the specific ways of understanding, categorization the world. The author accords basic attention to the active underlying stems or formants of the analyzing units. The importance of the ways of nomination was shown in the paper.